2021
DOI: 10.1186/s12906-020-03172-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of qigong on systolic and diastolic blood pressure lowering: a systematic review with meta-analysis and trial sequential analysis

Abstract: Background The benefits of qigong for systolic and diastolic blood pressure (BP) reduction have been noted in previously published systematic reviews; however, the data on its effectiveness has been at best scarce. We aimed to update the evidence of qigong on blood pressure reduction after taking into consideration the risks of random error and reliability of data in the cumulative meta-analysis using trial sequential analysis (TSA). Methods Includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Lee et al (2003) found that "Qigong" promotes the relaxation and stabilization of the sympathetic nervous system in hypertension patients, positively modeling urinary catecholamine levels and blood pressure, and improving ventilatory functions [180]. Recent systematic reviews on the subject confirm these results [206,207]. Controlled studies developed by Lan et al (2004) to access the cardioventilatory behavior of elderly "Qigong" and "Taijiquan" practitioners showed an improvement in aerobic capacity [185].…”
Section: Physiological Effects and Mechanisms Of "Qigong" Practicementioning
confidence: 95%
“…Lee et al (2003) found that "Qigong" promotes the relaxation and stabilization of the sympathetic nervous system in hypertension patients, positively modeling urinary catecholamine levels and blood pressure, and improving ventilatory functions [180]. Recent systematic reviews on the subject confirm these results [206,207]. Controlled studies developed by Lan et al (2004) to access the cardioventilatory behavior of elderly "Qigong" and "Taijiquan" practitioners showed an improvement in aerobic capacity [185].…”
Section: Physiological Effects and Mechanisms Of "Qigong" Practicementioning
confidence: 95%
“…The practice of qigong reduces the systolic and diastolic blood pressure in comparison with those of control groups [ 6 , 50 , 51 ]. Qigong may be an alternative non-pharmacological strategy for hypertension management, namely, in an elderly population group that usually takes too many medications [ 6 ].…”
Section: Yoga and Qigong In Health And Diseasementioning
confidence: 99%
“…The practice of qigong reduces the systolic and diastolic blood pressure in comparison with those of control groups [ 6 , 50 , 51 ]. Qigong may be an alternative non-pharmacological strategy for hypertension management, namely, in an elderly population group that usually takes too many medications [ 6 ]. In patients in an early stage of recovery from stroke, qigong showed more changes than conventional respiratory training in the improvement of trunk control ability, respiratory muscle functions, and ability to perform daily life tasks [ 52 ].…”
Section: Yoga and Qigong In Health And Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As the prototype of the traditional Chinese Qigong exercise routine, Mawangdui Guidance has a very long history, which can date back to the Qin and Han dynasties in China (221 BC-220 AD). [9] Some research indicated that Mawangdui Guidance plays an important role in preventing diseases and maintaining health, [10][11][12] even in preventing dementia in the old. [13,14] The practice of Mawangdui Guidance includes 12 movements and it takes about 7 minutes to do full set of exercises, which is challengeable for patients to learn a full set of movements.…”
Section: Introductionmentioning
confidence: 99%